EFEKTIVITAS KERJASAMA SISTER CITY KOTA SEMARANG (INDONESIA) DENGAN BRISBANE (AUSTRALIA) TAHUN 2002-2007 - Eka Titiyani A.; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
This sister city cooperation has background because of internationalrelation cooperation that in the beginning, it has come from intercity cooperationin Europe and United States since 1950’s. The first concept implementation is ascountry politic, economic diplomatic tool in regional and international level. Theimplementation becomes support for people to create fellowship and constructivecooperation, both interelement of society, city, local and central intergovernementand interstate in the whole wide world. This sister city cooperation is a goodbridge that is really needed by developing countries, like Indonesian withAustralia.This research is done by using descriptive analysis method. Thedescriptive analysis research meaning is describing, explaining researchsubject/object based on the data where the research began from general things,explained by collecting, arranging, and interpreting data based on this thesisclassification. The data collecting technique uses library research by varioussources like: book, journal, magazine, document, essay etc. The researcher alsouse internet media as source of data, because researcher limitation to findoriginal data.This research result described that this sister city cooperation affectivityruns well, but not all aspects that are concluded in the agreement run affectively.This cooperation still needs to be developed so all planned aspects run well. Andthe symbol needs to be made from sister city cooperation of Semarang andBrisbane so that the cooperation relation run can run well in these both cities.Keywords: Sister city, political and economic benefits, international cooperation